2017
DOI: 10.1080/01480545.2017.1405970
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal instability and cytotoxicity induced by ribavirin: comparative analysis in cell lines with different drug-metabolizing profiles

Abstract: Ribavirin is an important component of the treatment for hepatitis C virus (HCV) infection and, in combination with the new direct-acting antiviral (DAA) agents, comprises the major current therapeutic regimens. This study evaluated the cytotoxicity and chromosomal instability induced by ribavirin using the in vitro cytokinesis-block micronucleus cytome (CBMN-Cyt) assay in two cell lines with different expression levels of drug-metabolizing enzymes: human hepatocellular carcinoma cells (HepG2) and Chinese hams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…It is possible that these results were caused by RBV. In vitro genotoxicity studies using cultured human lymphocytes (Joksić et al 2000(Joksić et al , 2006, CHO-K1 (Chinese hamster ovary), and HepG2 cells (Librelotto et al 2019) also demonstrated that different RBV concentrations inhibit cell proliferation. It has been proposed that the cytotoxic effect of RBV is due to induction of cell death and suppression of cell division and proliferation (D'Souza & Narayana 2002).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is possible that these results were caused by RBV. In vitro genotoxicity studies using cultured human lymphocytes (Joksić et al 2000(Joksić et al , 2006, CHO-K1 (Chinese hamster ovary), and HepG2 cells (Librelotto et al 2019) also demonstrated that different RBV concentrations inhibit cell proliferation. It has been proposed that the cytotoxic effect of RBV is due to induction of cell death and suppression of cell division and proliferation (D'Souza & Narayana 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Two independent experiments, in duplicate, were performed. Data about treatment of HepG2 cells with RBV alone were previously published by our research group (Librelotto et al 2019).…”
Section: Cell Line and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic instability has various causes, of which chromosomal instability (CIN) and microsatellite instability have received the most focus (6). In CRC, CIN is the most common form of genomic instability, which occurs in nearly 80–85% of patients with CRC (7). Current research in the field is focused on elucidating the molecular basis of CIN, including the possible roles of defects in the spindle checkpoint and other regulators of mitosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, viral polymerases exhibit low replication fidelity, enabling them to overcome antiviral treatment modalities through rapid generation of resistance mutations . Resistance to antivirals has been widely observed for human immunodeficiency virus (HIV), hepatitis B virus, influenza virus, and many other RNA viruses, emphasizing the challenge for developing novel, long-lasting treatments. , In addition, host cell dependence is a requirement for virus replication, yet targeting host factors can result in cytotoxicity and severe side effects in patients . The recent COVID-19 pandemic highlights the aforementioned challenges of designing therapies against viruses, especially considering the prospect of preparing for the next virus outbreak of unknown origin.…”
mentioning
confidence: 99%